Modal Sosial Masyarakat Jalawastu Dalam Membangun Integrasi Sosial Dengan Pemerintah Daerah - Subiyanto Subiyanto; Wahyu Jati Kusuma; R Samidi; Enkin Asrawijaya (Journal of Social Politics and Governance (JSPG), 2022)
The purpose of this study is to find out how the social capital built by the Jalawastu community is able to build consensus with the local government. Harmony through integration is the key word developed by the people of Jalawastu with the world outside their community, especially with the local government. This research method will use James P. Spradley's "Gradually Forward Research Pathway", which is based on five principles, namely single technique, problem identification, gradual progress, original research, and problem solving. This research will use the functional structure paradigm. This research is an ethnographic type with a qualitative approach. Collecting data through in-depth interviews, observation, and documentation. The analysis begins after the field data is recorded in field notes, then the data is analyzed qualitatively to produce a thick description. The validity of the data is used by triangulation. Data analysis was carried out thematically, textually, contextually and interpretation results.